The Effect of Asset Efficiency and Growth on Financial Performance in the Defense Industry Sector - Amanda, Brian; Saputro, Guntur Eko (Graduate Program Magister Manajemen Pendidikan, 2023)
This research focused on three defense industry companies, namely PT Dirgantara Indonesia, PT PAL Indonesia (Persero) and PT Pindad (Persero). This study used a quantitative research approach with a time period from 2011 to 2020. The results of the study show that the magnitude of the effect of efficiency and asset growth on financial performance in the defense industry sector is 45.0% and the remaining 55.0% is explained by other variables not examined in this study. Efficiency and Asset Growth have a simultaneous effect on Financial Performance in the Defense Industry Sector. Efficiency partially has a positive effect on Financial Performance in the Defense Industry Sector. Asset Growth partially does not affect Financial Performance in the Defense Industry Sector. This can be a concern for companies in the defense industry sector so that Indonesia can create a strong, independent and competitive defense industry. Keywords: Efficiency, Global, Financial Performance, Asset Growth, Technology